Quantitative Texture Analysis of Spark Plasma Textured n‐Bi2Te3. Issue 7 (22nd May 2014) - Lognoné, Quentin; Gascoin, Franck; Lebedev, Oleg I.; Lutterotti, Luca; Gascoin, Stéphanie; Chateigner, Daniel; Zhou, X.‐D.
<x xml:space="preserve">Abstract</x> For the first time, the quantitative texture analysis of edge free sintered Bi2Te2.4Se0.6 samples elaborated by high‐energy ball milling and Spark Plasma Texturing is performed. As expected, due to the structural anisotropy, the forging process results in a significant decrease in electrical resistivity perpendicularly to the uniaxial stress field. Surprisingly, this also leads to a large decrease in the lattice thermal conductivity in this direction. Crystallite boundaries amorphization as evidenced by transmission electron microscopy explains this latter decrease due to the friction induced by the applied pressure and grains sliding on each other during reorientation. X‐ray diffraction also evidences development of strong crystallite size anisotropy and more isotropic microstrain developments under pressure, simultaneously favoring electronic conduction and phonon scattering, respectively. The thermoelectric performance is thus increased, however, the quantitative texture analysis demonstrates that the enhanced texture is only slightly responsible for the improved performance that rather comes from a peculiarly engineered microstructure.